2003
DOI: 10.1063/1.1617374
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting nanocrystalline iron disilicide thin films prepared by pulsed-laser ablation

Abstract: Amorphous iron silicide was reported to be semiconducting as well as β-FeSi2, and it has received considerable attention from both the physical and engineering points of view. However, there have been few studies and its basic properties are still unknown. We could grow the semiconducting nanocrystalline iron disilicide thin films by pulsed-laser deposition using an FeSi2 target. They consist of crystallites with diameters ranging from 3 to 5 nm. The carrier density and the mobility at 300 K were 1.5×1019 cm−3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 11 publications
1
43
0
Order By: Relevance
“…10,12,18 However, when a highly energetic pulsed laser deposition technique is used, 8,19 the films grow in the form of a nanocrystalline ␤-FeSi 2 phase already at RT. In the studies of this technique for deposition of ␤-FeSi 2 it was suggested 19 that diffusivity of Si atoms is dominant for substrate temperatures ജ400°C, and diffusivity of Fe atoms is enhanced for substrate temperatures ജ700°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12,18 However, when a highly energetic pulsed laser deposition technique is used, 8,19 the films grow in the form of a nanocrystalline ␤-FeSi 2 phase already at RT. In the studies of this technique for deposition of ␤-FeSi 2 it was suggested 19 that diffusivity of Si atoms is dominant for substrate temperatures ജ400°C, and diffusivity of Fe atoms is enhanced for substrate temperatures ജ700°C.…”
Section: Discussionmentioning
confidence: 99%
“…7 Amorphous FeSi 2 is also a direct gap semiconductor with a band gap of 0.88-0.90 eV, close to that of the crystalline ␤ phase, and with a similar photoabsorption efficiency. More recently, 8 it was reported that very fine ͑3-5 nm͒ nanocrystalline ␤-FeSi 2 films also exhibit a direct band gap behavior. As their structure is somewhere at the boundary between a fully grown crystalline and the amorphous FeSi 2 phase, the measured E g = 0.85-0.95 eV confirms similar band gap values for these two phases.…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned in the Introduction, amorphous semiconducting Fe disilicide can be grown, e.g., by sputter deposition. Fe-Si bonds are identified via XPS measurements or electron diffraction [18,[44][45][46][47][48][49].…”
Section: Fe Ni Mo and W Surfactantsmentioning
confidence: 99%
“…Pronounced phase separation also takes place in ion beam irradiation induced cone formation on compound semiconductors like InSb or GaSb [42,43]. Usually, metal silicides are considered as crystalline phases, however, amorphous Fe disilicide has attracted attention as a semiconducting material with a band gap of 0.9 eV with potential applications as photovoltaic material [44][45][46]. The identification of amorphous metal silicides can be done on the basis of X-ray photoelectron spectroscopy (XPS) or an analysis of atom pair distribution function measured with electron diffraction [18,[47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Milosavljevic presented a thermodynamic calculation, which indicates, that amorphous FeSi 2 is in metastable equilibrium with Si and should have a nearly constant stoichiometry of Fe/Si ≈ 1/2. 24 However, little work has yet been done to reveal the atomistic structure of amorphous FeSi 2 .…”
mentioning
confidence: 99%